Pollen Analysis of the Honeys Samples Produced in the Three Phyto-geographical Zones of Benin - Azonwade, François Ezin; Paraïso, Armand; Tossou, Monique G.; Sina, Haziz; Kelomey, Aude Eminsede; Chabi-Sika, Kamirou; Baba-Moussa, Lamine (European Scientific Journal, ESJ, 2017)
The aim of this work was the melissopalynologycal analysis of the honey samples collected both during the dry and rainy seasons of the three phyto-geographical zones of Benin. The analysis was performed by conventional methods on 60 honeys samples. The total of 138 taxa have been identified at family level (31), genus level (20) and to the level species (87). The number of pollens counted varies according to the phyto-geographical zones. Thus, 17091 pollens have been counted in the samples of the Sudanian zone; 13884 in those of the Sudano-Guinean zone and 7960 pollens in those of the Guinean zone. The pollen content of the honey samples reflects the plant species of the three phyto-geographical zones. The most dominant plant taxa were Combretaceaes (26.01%) and Parkia biglobosa (10.67%) in Sudanian zone, Combretaceae (29.52%) in SudanoGuinean zone. In the Guinean zone, the dominant taxa were Zea mays (18.35%) and Terminalia (15.34%). The specific richness varies from 6 to 43 in the Sudanian zone, from 7 to 34 in the Sudano-Guinean zone and from 1 to 28 taxa in the Guinean zone. None of the density of the dominant pollens reached 45%, thus all the analyzed honeys are polyfloral.